2018
DOI: 10.1021/acs.jpcc.8b02104
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Scale Insights into Electrochemical Dissolution of Janus Pt–SnO2 Nanoparticles in the Presence of Ethanol in Acidic Media: An IL-STEM and EFC–ICP–MS Study

Abstract: The studies on Pt-or Pt alloy-based catalysts for ethanol oxidation have been focused mostly on their activity, with much less emphasis on their stability. Dissolution of commercial Pt−SnO 2 /C electrocatalyst for direct ethanol fuel cells was investigated on the atomic scale by employing two advanced electrochemical characterization techniques: (i) identical location scanning transmission electron microscopy (IL-STEM) and (ii) electrochemical flow cell connected to inductively coupled mass spectrometry (EFC−I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Since the inceptions of the methodology by K. J.J. Mayrhofer et al. ( Meier et al, 2012a , 2012b , 2014 ; Schlögl et al., 2011 ), the game of “Spot the difference” ( Scheme 2 ) ( Hodnik and Cherevko, 2019 ) has been recently re-defined to retrieve information at the atomic scale ( Jovanovič et al., 2018b ; Rasouli et al., 2019 ; Ruiz-Zepeda et al., 2019 ), adapting it to something more close to a semi in-situ method. Crucially, atomic-resolution electron microscopy images provide much more information than just those recorded with a nanometer-scale resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Since the inceptions of the methodology by K. J.J. Mayrhofer et al. ( Meier et al, 2012a , 2012b , 2014 ; Schlögl et al., 2011 ), the game of “Spot the difference” ( Scheme 2 ) ( Hodnik and Cherevko, 2019 ) has been recently re-defined to retrieve information at the atomic scale ( Jovanovič et al., 2018b ; Rasouli et al., 2019 ; Ruiz-Zepeda et al., 2019 ), adapting it to something more close to a semi in-situ method. Crucially, atomic-resolution electron microscopy images provide much more information than just those recorded with a nanometer-scale resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Since no data on dissolution of non‐alloyed Pt/C was presented, it is not clear if this can be attributed to an improved sensitivity of the used setup alone or to any possible un‐stabilizing effect of Co (note that according to theoretical works presence of Co can be beneficial in stabilizing Pt). Platinum dissolution at lower potentials is known but typically attributed to the presence of complexing or destabilizing elements in the electrolyte . Another important observation is that at low potentials (E <0.9 V RHE ) anodic dissolution is the dominating mechanisms.…”
Section: On‐line Icp‐ms In Stability Studies Of Orr Electrocatalystsmentioning
confidence: 99%
“…In addition to the commercial materials discussed in this work, our experience with STEM analysis of carbon-supported catalysts suggested that atomic species are indeed a common companion to metal nanoparticles. For example, we detected single atoms in a commercial PtRu/C catalyst [38] and commercial Pt-SnO 2 /C catalyst [39] on a high-surface area nitrogen-doped carbon alongside Pt nanoparticles [32] and on a graphite rod after electrochemical deposition of Ag [40].…”
Section: The Images Inmentioning
confidence: 99%